Distortion Parameters Analysis Method Based on Improved Filtering Algorithm - ZHANG Shutuan; LI Yan; WANG Jing; WU Hengzhou (Institute of Advanced Engineering and Science, 2013)
In order to realize the accurate distortion parameters test of aircraft power supply system, and satisfy the requirement of corresponding equipment in the aircraft, the novel power parameters test system based on improved filtering algorithm is introduced in this paper. The hardware of the test system has the characters of s portable and high-speed data acquisition and processing, and the software parts utilize the software Labwindows/CVI as exploitation software, and adopt the pre-processing technique and adding filtering algorithm. Compare with the traditional filtering algorithm, the test system adopted improved filtering algorithm can help to increase the test accuracy. The application shows that the test system with improved filtering algorithm can realize the accurate test results, and reach to the design requirements. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3416